Long Noncoding RNA ASLNC07322 Functions in VEGF-C Expression Regulated by Smad4 during Colon Cancer Metastasis - Xuemei Li; Xiaohong Lv; Zhuowei Li; Chao Li; Xinlei Li; Jianbing Xiao; Baoquan Liu; Huike Yang; Yafang Zhang (Elsevier, 2019)
Deletion and mutation of the Smad4 gene are favorable events for the progression of colon cancer, which is related to the negative regulation of vascular endothelial growth factor C (VEGF-C). However, the regulatory mechanism between Smad4 and VEGF-C remains unclear. We reported first that Smad4 can increase the transcription of miR-128-3p, a microRNA targeting VEGF-C mRNA, resulting in a negative correlation between Smad4 and VEGF-C. Moreover, we found that Smad4 combined with Smad3 can positively regulate VEGF-C during colon cancer metastasis through binding to VEGF-C gene promoter. Further, results revealed a mechanism that long noncoding RNA (lncRNA) ASLNC07322 increased specifically in metastatic colon cancer and decreased miR-128-3p as a sponge, leading to a subsequent elevation of VEGF-C. In a word, there are two pathways in the progression of colon cancer, including Smad4/miR-128-3p/VEGF-C and Smad4/VEGF-C pathways in non-metastatic and metastatic colon cancer, respectively. ASLNC07322 crucially controlled this negative and positive regulatory transformation between them. Additionally, ASLNC07322 knockdown combined with Smad4 overexpression could efficiently inhibit lymphatic endothelial cells (LECs) proliferation and tube formation in vitro, as well as tumor growth and lymphangiogenesis in vivo. These data explained the underlying mechanism of Smad4 contribution on VEGF-C expression during metastasis where ASLNC07322 functions vitally as a switch in colon cancer. Keywords: colon cancer, VEGF-C, lncRNA ASLNC07322, miR-128-3p, Smad4